Bisexual People's Utilization of Sexual Health Services at an LGBTQ Community Center in Chicago. Issue 3 (2nd July 2020) - Holmes, Nicole; Beach, Lauren B.
Abstract: Bisexual people are at increased risk for sexually transmitted infections (STIs), including HIV. In STI data collection, bisexual people are often miscategorized as or conflated with heterosexual or gay/lesbian people. Such poor data capture practices invisibilize bisexual people and prevent the tailoring of HIV and STI services to cater to bisexual populations. The Center on Halsted (COH) is an LGBTQ community center in Chicago. COH's HIV & STD Services Department provides HIV testing to people who present for HIV screening services age 12 and older. COH also administers the State of Illinois AIDS, HIV, & STD Hotline. This manuscript reports HIV-related service access patterns of COH clients by sexual identity, with an emphasis on reporting patterns among bisexual and other non-monosexual (e.g., "bi+") populations in comparison with other sexual minority populations. Among COH's HIV testing clients who were sexual minorities in fiscal years 2018 and 2019, 15.42% in 2018 and 16.71% in 2019 identified as bisexual, respectively. Among sexual minority hotline callers, approximately one quarter (25.1% in 2018 and 28.8% in 2019) identified as bisexual. Given that bisexual individuals comprise over half of sexual minority populations, these findings indicate that bi + individuals may be under-represented in accessing HIV and STI services at COH. These results provide previously unknown insight into the sexual identities of populations accessing HIV- and STD-related services within a LGBTQ community setting. Funders of HIV and STI surveillance services should change reporting requirements to make visible the HIV services access patterns and outcomes of bisexual populations.